1989
DOI: 10.1177/019262338901700102
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms in the Response of the Arterial Wall to Injury and Repair

Abstract: This synopsis emphasizes the inappropriateness of a "single stimulus-single response" approach in understanding the response of the arterial wall to injury and repair. The outcome of any injurious stimulus is a series of interactive cascades among the endogenousand exogenous cellular and non-cellular components of the arterial wall, and the cellular and non-cellular elements of the blood. Both genetic and hemodynamic factors can further influencethis response. The more prominent of the cellular and non-cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This cellular population dramatically changes during HA when PMNs increase markedly (about 5 × 10 6 -10 7 /mL). These cells produce ROS, when activated by various proinflammatory mediators (Røkke et al 1989, Botha et al 1995, which are released from endothelial cells and locally-recruited platelets after intraarticular vascular injury (Schwartz et al 1989). Several investigators have studied the damage to cartilage matrix and chondrocytes caused by activated PMNs, which are thought to augment the degradation of elastase (Weiss and Regiani 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This cellular population dramatically changes during HA when PMNs increase markedly (about 5 × 10 6 -10 7 /mL). These cells produce ROS, when activated by various proinflammatory mediators (Røkke et al 1989, Botha et al 1995, which are released from endothelial cells and locally-recruited platelets after intraarticular vascular injury (Schwartz et al 1989). Several investigators have studied the damage to cartilage matrix and chondrocytes caused by activated PMNs, which are thought to augment the degradation of elastase (Weiss and Regiani 1984).…”
Section: Discussionmentioning
confidence: 99%
“…These cells have the ability to produce catabolic enzymes, cytokines, and reactive oxygen species following activation by different proinflammatory mediators such as platelet activating factor, thromboxan-A2, and leukotriens (LTB4). 15,16 These activators are released from the endothelial cells and from the locally recruited platelets 17 as a consequence of the intraarticular vascular injury. 18 However, the effect of supposed inflammatory mediators on leukocytes has not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are an important source of 2 major prothrombotic mechanisms, PCA and O2 [19][20][21], In addition, a recent report showed that D affects the O 2 generation by granulocytes [22], Therefore, we suspected that the antithrombotic effectiveness of D might involve a direct effect on monocytes. Our data indicate that the drug weakly af fects the generation of monocyte PCA, while it has the potential to inhibit the O2 genera tion in response to stimuli that affect cal cium movements.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other directions were explored. Current evi dence indicates that monocytes/macrophages play a major role in hemostasis and thrombosis through their ability to express procoagulant activity and generate oxygen free radicals O 2 [19][20][21]. Together with the information that D affects the generation of superoxide anion by granulocytes [22], this concept prompted us to evaluate whether D had any effect on monocytes, and the present paper reports the relevant data of the study.…”
Section: Introductionmentioning
confidence: 98%